Upaya Meningkatkan Minat Belajar Siswa dengan Model Pembelajaran Tipe STAD pada Pelajaran Agama Katolik - Kosmas Erik Kuhek; Fabianus Sidi; Yohanes Yuda (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2018)
The aim of the study was, to know much whether the application of the Cooperative learning model STAD in the Catholic Religion class can increase the students interest. The approach used in this study was, The Student’s Team Achievement Division. The respondent of this study was 28 persons. The performance indicator used in this study was if ≥ 80% of the students can comprehend the material of “Memperjuangkan Keadilan” and ≥ 80% of the students got increase on the learning interest. The result of the study in cycle on with the percentage of the students learning interest reached the average of 60% and in cycle two got increase on the students learning interest reached the average of 80%, While the result of the students learning result in cycle one reached the average of 60%, and in cycle two reached the average of 82%. Based on the result of the study which has been gained it can be concluded that the application of the method of STAD in the Catholic Religion class can really increase the students learning.